When Hindsight Is Not 20/20: Ecological Momentary Assessment of PTSD Symptoms Versus Retrospective Report. (January 2021) - Schuler, Keke; Ruggero, Camilo J.; Mahaffey, Brittain; Gonzalez, Adam; L. Callahan, Jennifer; Boals, Adriel; Waszczuk, Monika A.; Luft, Benjamin J.; Kotov, Roman
Assessment of posttraumatic stress disorder (PTSD) has relied almost exclusively on retrospective memory of symptoms, sometimes over long intervals. This approach creates potential for recall bias and obscures the extent to which symptoms fluctuate. The aim of the present study was to examine the discrepancy between retrospective self-reporting of PTSD symptoms and ecological momentary assessment (EMA), which captures symptoms closer to when they occur. The study also sought to estimate the degree to which PTSD symptoms vary or are stable in the short-term. World Trade Center responders ( N = 202) oversampled for current PTSD (19.3% met criteria in past month) were assessed three times a day for 7 consecutive days. Retrospective assessment of past week symptoms at the end of the reporting period were compared with daily EMA reports. There was correspondence between two approaches, but retrospective reports most closely reflected symptom severity on the worst day of the reporting period rather than average severity across the week. Symptoms varied significantly, even within the span of hours. Findings support intervention research efforts focused on exploiting significant, short-term variability of PTSD symptoms, and suggest that traditional assessments most reflect the worst day of symptoms over a given period of recall.